The challenges of universal primary education in Uganda through distance education programmes - Aguti, Jessica N.; Fraser, William J. (Africa Education Review, 2005)
This article reports on teacher education in Uganda, with specific reference to the role that distance education has played in upgrading the quality of education in general and in supplying more qualified teachers to meet a growing demand, specifically for teachers involved in primary education. The investigation paves the way for the establishment of the Open University of Uganda and illustrates how the Primary Education Policy of Uganda has increased access to 7 million primary school learners to schools in 2002. The article also explains how the qualifications of 10 000 in-service teachers have been upgraded between 1995 and 2000. The successes of two major in-service teacher education programmes are discussed. The article also explains how the Mubende Integrated Teacher Education Project (MITEP) not only contributed to the training of teachers, but also focused the attention of educators on the possibiliities of distance education for Uganda. Furthermore, it also argues that the Northern Integrated Teacher Education Project (NITEP) has on the other hand achieved successes in the field of inservice teacher education. The programmes assisted in the training of academic support staff who work in distance education. The article concludes by addressing the further needs of distance education in Uganda and highlights the challenges facing distance education programmes in Uganda.
Keywords: Academic support; Achievements; Challenges; Distance education; Open learning; Teacher education